Autoimmune limbic encephalitis due to Hashimoto's encephalopathy responding to therapeutic plasma exchange: A case report. Issue 5 (11th July 2021) - Ohnmar, Ohnmar; Win, Sai Kyaw; Tun, Zin Phyu; Aye, Yin Minn; Lwin, Thandar; Lay, Phyu Phyu
Abstract: A 66 years‐old lady presented with acute onset confusion and status epilepticus. MRI (Brain) showed T2 shine through at bilateral hippocampi. Cerebrospinal fluid revealed mild lymphocytic pleocytosis. Screening for infections, autoimmune and paraneoplastic conditions were negative except significantly high anti‐TPO antibody and hyperthyroid state. Her seizures needed multiple antiepileptic drugs. Limbic encephalitis was treated with high‐dose steroid but not responded and plasma exchange was proceeded. At two weeks after plasma exchange, her conscious level and seizure frequency were significantly improved. We present a case of Hashimoto's encephalopathy presenting with limbic encephalitis not responding to steroid but to plasma exchange.